Avaliação da perda óssea alveolar em pacientes encaminhados à especialista em periodontia: estudo radiográfico - Kerbauy, Warley David [UNESP] (1999)
The aim of this study was to evaluate the mean of alveolar bone loss (%) in radiographies of patients referred to specialist for periodontal treatment. Full mouth series of periapical radiographies (paralelism technique) were used. A total of 9808 proximal surfaces in 4804 teeth of 213 patients (90 males and 123 females), mean age, 44.3 years, were assessed. The alveolar bone loss was measured in relation to root lenght expressed as an average similar to Schei 's technique (1959) without the use of ruler. The references used were the distances cement-enamel juntion (CEJ) - alveolar crest (AC) and CEJ- dental apex taken with a digimatic caliper. The results showed that the mean values of alveolar bone loss (%ABL) was 22.39%. Men showed higher mean values of %ABL than women; the %ABL increased with the age, but the difference among age groups was no statistical significant (p>0.05); the mean values of %ABL of distal surfaces was higher than mesial surfaces (p<0.01), ríght quadrants exhibited higher %ABL values than left quadrants (p<0.01); maxillary sites showed mean values of %ABL higher than mandibular sites; the highest mean values of %ABL was found in molar group, followed by incisor groups, and premolar group; the canine group exhibited lower mean values of %ABL; the differences among the groups was considered statitistically significant (p<0.01). lt was suggested the usage of this technique in the dentistry offices and radiological services for the patient 's documentation and assortment and for later comparison about alveolar bone level